Reviews of recent publications - various authors (Studies in 20th & 21st Century Literature, 1993)
Gilbert, Sandra M. and Sagan Gubar. Blindspots of an Old Dream of Equality: Liberal Feminism as Exclusionary Practice in No Man's Land Trinh, T. Minh-ha. Woman, Native, Other. Writing Postcoloniality and Feminism by Charles J. Stivale Waelti-Walters, Jennifer. Feminist Novelists of the Belle Epoque: Love as a Lifestyle by Christiane P. Makward
Keywords: Sandra M. Gilbert; Sagan Gubar; Blindspots of an Old Dream of Equality: Liberal Feminism as Exclusionary Practice in No Man& #x27; s Land; T. Minh-ha Trinh; Woman Native Other. Writing Postcoloniality and Feminism; Jennifer Waelti-Walters; Feminist Novelists of the Belle Epoque: Love as a Lifestyle; Charles J. Stivale; Christiane P. Makward